Pemikiran dan Aspek Lokalitas Tafsir Al-Ibrīz Karya Kh. Bisri Mustofa - Maksum, Ghufron; Afiyah, Nur (STAINI Press, 2023)
This paper aims to examine the thoughts and aspects of the locality of Tafsir al-Ibrīz which is the work of an Indonesian scholar named KH. Bisri Mustofa. The research method used in this study is a literature study with a qualitative research type. The data sources used consist of primary sources in the form of Tafsir al-Ibrīz texts and secondary sources in the form of books, articles, and other relevant writings. Data collection was carried out through literature review, while data analysis used analytical descriptive methods. The results of the study show that Tafsir al-Ibrīz was written using the ijmālī method with the style of tafsir adabi ijtima'i, and presented with a fiqh and Sufism approach. Pemikiran KH. Bisri Mustofa in tafsir al-Ibriz includes an understanding of faith in supernatural matters, interpretation of sharia law, and the importance of morals in religious practice. The locality aspect of this tafsir is reflected in the use of Javanese Pegon as the author's daily language, as well as the application of ethical uploads in the presentation of texts. Despite the advantages and disadvantages, this interpretation received a positive response and comments from the community, as can be seen from the enthusiasm of the community in participating in studies in various Islamic boarding schools. Tafsir al-Ibrīz is not only a work of tafsir, but also an important cultural heritage in the understanding of Islam in Indonesia